Potencial funcional de bebidas lácteas fermentadas sem lactose adicionadas de culturas probióticas e polpa de Syzygium cumini (L.) Skeels - Garcia, Sabrina Laís Alves (2019)
The use of whey in the production of a fermented dairy beverage added with probiotic microorganisms and fruit pulps seems to be a promising alternative for the development of a functional food. The hydrolysis of lactose can be performed in order to increase the target audience, taking into account those intolerant to this disaccharide. The mean composition, microbial viability, storage stability, sensory acceptability, protein profile and antioxidant capacity parameters were determined in three lactose-free fermented dairy beverages using Streptococcus thermophilus TA40 as starter culture and added with Syzygium cumini (jambolan) pulp with the objective of to obtain the functional potential of these products. The control beverage T1 was produced without adjuvant lactobacilli; the second (T2) and the third (T3) were added, respectively, of potentially probiotic cultures Lactobacillus rhamnosus LR32 and Lactobacillus casei BGP93, respectively, as adjuvant microorganisms. The beverages achieved a protein content in accordance with the required by Brazilian legislation (higher than 1.0 g 100 g^-1), fat content enough to classify them as ―low‖ in this nutrient (below than 3 g 100 g^-1), and viability higher than 7 log UFC g^-1 for both lactobacilli, which did not influence the population of the starter microorganism (S. thermophilus). There was post-acidification in all trials since the pH reduced significantly over the storage (p<0.05). The beverage presented mean overall acceptability above 6.0 and no significant difference was observed between trials and storage days (p>0.05). Color was the best evaluated parameter by the judges, with average scores varying from 7.35 to 8.29, with no significant differences between trials (p>0.05). Therefore, post-acidification during the storage period did not affect the viability of the lactic acid bacteria, the acceptability and color of the products. The phenolic content and the total antioxidant capacity of the products increased significantly (p<0.05) after the addition of the jambolan pulp, and the later parameter remained significantly increasing throughout the storage (p<0.05), probably due to the proteolysis process. The dairy beverages produced in this study are seen as good functional food options in reason of their nutritional value, viability of potential probiotic lactobacilli, total phenolic content and antioxidant capacity obtained.